A new species of Mesostenus Gravenhorst (Hymenoptera: Ichneumonidae: Cryptinae) from Colombia - Herrera-Florez, Andres Fabian; Diaz, John Alexander Pulgarin; Quiroz-Gamboa, Jhon A. (Zootaxa, 2017)
The genus Mesostenus Gravenhorst has sixty one described species worldwide. A new species, Mesostenus hypsipylaphagous Herrera-Florez, sp. n. is described and its host given. This is the first record of Mesostenus from Colombia.